2018
DOI: 10.1134/s1070363218040345
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New 1,4-Benzodioxanуl-1,2,4-triazole Derivatives

Abstract: The reaction of 5-(1,4-benzodioxan-2-yl)-4H-1,2,4-triazole-3-thiol with N-substituted chloroacetic acid amides obtained by condensation of chloroacetyl chloride with various primary amines furnished a series of S-amidomethyl derivatives. The corresponding thiazolotriazolone prepared from 2-[5-(1,4-benzodioxan-2yl)-4H-1,2,4-triazol-3-ylthio]acetic acid reacted with aromatic aldehydes to form arylidene derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The authors [16] reported the synthesis of new derivatives of 1,2,4-triazole with benzodioxane in the fifth position. The desired amidomethylthio derivatives were synthesized by replacing the potassium salt of triazolotyol with various primary arylalkylamines [16] (Fig. 15).…”
Section: Figure 11 Synthesis Of N-and S-triazologlycosides [12]mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors [16] reported the synthesis of new derivatives of 1,2,4-triazole with benzodioxane in the fifth position. The desired amidomethylthio derivatives were synthesized by replacing the potassium salt of triazolotyol with various primary arylalkylamines [16] (Fig. 15).…”
Section: Figure 11 Synthesis Of N-and S-triazologlycosides [12]mentioning
confidence: 99%
“…Transformation of 1,4-benzodioxanyl-1,2,4-triazoles [16] According to the authors [16], derivatives of 5-(1,4-benzodioxanyl)-1,2,4-triazole-3-thiol have antitumor effects. The compounds also showed antimicrobial and antiviral effects.…”
Section: Figure 15mentioning
confidence: 99%